Enhancing farmer linkages to markets in developing countries through mapping of supply chains and optimising transport. (March 2023) - Higgins, Andrew; Bruce, Caroline; McFallan, Stephen; Chilcott, Chris; McKeown, Adam; Williams, Liana; Ackerman, John; Wulandari, Dian Yuanita; Dyer, Rodd; Le, Nga
Highlights: Freight movement in Indonesia and Vietnam is characterised by high transport and logistics costs. The Transport Network Strategic Investment Tool (TraNSIT) developed by CSIRO was used to map freight movement for agriculture supply chains in Indonesia (rice, cattle) and Vietnam (maize, cassava) Stakeholders were integral to determining and mapping supply chains for studied commodities, providing core datasets, expert opinion and validation of outputs. Case studies to model route changes due to road closures provided information on changes in supply chain transport routes and costs, demonstrating the value of the tool in exploring 'what if' scenarios. Abstract: Getting products to market where transport infrastructure is underdeveloped or unreliable is a major barrier to agricultural development, particularly in less-developed countries. Transport represents a high proportion of farm gate costs of moving livestock and crops to processors and local markets throughout the region. This is confounded by poor transport network infrastructure throughout the supply chain, wet weather accessibility constraints, food losses in transit, and congestion. Evidence-based approaches can inform transport and logistics infrastructure investments at different locations to maximise cost reductions. The Transport Network Strategic Investment Tool (TraNSIT) was developed by Australia's national science agency, the Commonwealth Scientific and Industrial Research Organisation (CSIRO), to map freight movement and associated costs. The tool was applied to create the largest supply chain analysis ever conducted in Australia, mapping more than 170 commodities and 25 million vehicle trips per year. It is used extensively by the Federal and state governments to inform over 5 billion per year in major infrastructure and freight strategies. Drawing on experience through an investment by the Australian Government in partnership with agencies in Vietnam and Indonesia, we show how the TraNSIT methods can be extended and implemented in these developing countries. Several challenges are addressed around securing commitment from key in-country ministries and state-owned enterprises, accessing quality data, and modelling freight and supply chains that differ considerably to those in developed countries. Applications to key cropping and livestock commodities are used to demonstrate how TraNSIT can be used to analyse existing supply chains and test scenarios for various infrastructure investments.